Pengaruh Harga Pakan Terhadap Produktivitas Ayam Ras Pedaging Di Indonesia - Ferdi Kurniawan; M. Rehan; Zali Wijaya Kesuma Mudafi; Aura Nabila; Kiagus Muhammad Zain Basriwijaya (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This research aims to analyze the relationship between feed prices and the productivity of broiler chickens in Indonesia, considering that poultry farming is the main source of animal protein needs for the community. One important component that influences production efficiency is feed prices, which often change due to changes in local and international markets. This research uses a quantitative analysis method with regression which is used in this research to find the relationship between the increase in feed prices and the level of productivity of broiler chickens, including body weight gain, feed efficiency and mortality rates. The data used includes feed prices, production costs and harvest yields from various regions in Indonesia during a certain time period. According to research results, the increase in feed prices made a significant contribution to the decline in broiler chicken productivity. These results indicate that to maintain production stability, strategies to manage feed costs and diversify local raw material sources are needed. In conclusion, to keep the poultry farming industry in Indonesia afloat, feed price stability is very important.